Effect of chestnuts level in the formulation of the commercial feed on carcass characteristics and meat quality of Celta pig breed - Carmen De Jesús (Spanish Journal of Agricultural Research, 2016)
The effect of including chestnuts in the formulation of the feed on carcass characteristics and meat quality from 24 castrated males Celta pigs was studied. The inclusion of 15% of chestnut (CH15) improved (p<0.01) the carcass (118 vs. about 104 kg) and live weights (149 vs. 133-139 kg). Killing out percentage was also better for chestnuts groups than for control group. With regards the morphometric parameters, there were no statistically significant (p>0.05) differences except for the carcass length and ham length, for which the CH15 group proved to be the group with the longest sizes. The diet did not affect the physicochemical properties (colour parameters, water holding capacity and shear force) of longissimus dorsi muscle. The composition of some fatty acids of the longissimus dorsi muscle was affected by diet. The total saturated (35-38%) and total polyunsaturated fatty acids (8-10%) did not present differences. However, the increase of chestnut in the diet increased (p<0.05) the monounsaturated fatty acids in intramuscular fat (57% in CH25 vs. 53% in control and CH15). Within monounsaturated fatty acids, the C18:1n9 was the most influenced by the diet. The expression of the enzyme that synthesizes C18:1n9 depend on the composition of the diet. Therefore, the lower content of protein and the higher amounts of C18:1n9 and C18:2n6 in the chestnut could be explaining the greater content of C18:1n9 in muscle of chestnut-fed animals. The main conclusion is that including chestnuts in the diet would allow reduce production costs with no effect or even improving carcass measurements and meat quality.